2010
DOI: 10.1192/bjp.bp.110.077289
|View full text |Cite
|
Sign up to set email alerts
|

Treatment adherence therapy in people with psychotic disorders: randomised controlled trial

Abstract: BackgroundInterventions to improve adherence to treatment in people with psychotic disorders have produced inconclusive results. We developed a new treatment, treatment adherence therapy (TAT), whose intervention modules are tailored to the reasons for an individual's non-adherence.AimsTo examine the effectiveness of TAT with regard to service engagement and medication adherence in out-patients with psychotic disorders who engage poorly.MethodRandomised controlled study of TAT v. treatment as usual (TAU) in 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
1
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 34 publications
1
89
1
9
Order By: Relevance
“…In early illness, a mirror image study showed reduction in relapse after therapy. 115 On the other hand, the trial by Staring et al 116 showed substantial improvement in adherence (but not insight), d = 0.48, after a complex intervention involving motivational interviewing for those with negative attitudes (87% of the participants) but with other techniques for those with poor response or those who were chaotic. One such technique is use of reminders.…”
Section: Rationale For Combining Online Psychoeducation Sms Remindermentioning
confidence: 98%
“…In early illness, a mirror image study showed reduction in relapse after therapy. 115 On the other hand, the trial by Staring et al 116 showed substantial improvement in adherence (but not insight), d = 0.48, after a complex intervention involving motivational interviewing for those with negative attitudes (87% of the participants) but with other techniques for those with poor response or those who were chaotic. One such technique is use of reminders.…”
Section: Rationale For Combining Online Psychoeducation Sms Remindermentioning
confidence: 98%
“…Est谩 basada en un modelo emp铆rico que agrupa los determinantes de la falta de adherencia en tres categor铆as: (1) falta de Insight y rechazo del tratamiento, (2) insatisfacci贸n con la medicaci贸n y (3) carencia de habilidades cognitivas necesarias para realizar correctamente el tratamiento farmacol贸gico, e incorpora un m贸dulo de intervenci贸n para cada uno de ellos: (a) entrevista motivacional, (b) adaptaci贸n de la medicaci贸n y (c) t茅c-nicas de entrenamiento conductual (Staring et al, 2010).…”
Section: Terapia De Adherencia Al Tratamientounclassified
“…Dos ensayos cl铆nicos evidenciaron que la intervenci贸n produc铆a una reducci贸n significativa de la sintomatolog铆a de los sujetos pero no mejoraba la adherencia a la medicaci贸n (Shulz et al, 2013), mientras que un estudio realizado en 2013 puso de manifiesto que la intervenci贸n motivaba una reducci贸n significativa de las tasas de reca铆da, pero no aport贸 datos sobre la adherencia a la medicaci贸n (Brown, Gray, Jones & Whitfield, 2013). Finalmente, tres pruebas controladas aleatorizadas mostraron resultados significativos en el incremento de la adherencia terap茅utica en favor de la TAT (Staring et al, 2010;Chien, Mui, Cheung & Gray, 2015;Dikec & Kutlu, 2016).…”
Section: Terapia De Adherencia Al Tratamientounclassified
“…Hospitalizaci贸n: Se evaluaron los resultados de un estudio realizado en 54 pacientes en el grupo de terapia de adherencia y 55 en el de tratamiento usual 19 , la calidad se clasific贸 como muy baja por el riesgo de sesgos y las bajas precisi贸n y consistencia. El resultado se mostr贸 a favor de la intervenci贸n pero no fue estad铆sticamente significativo (RR 0,65; IC95% 0,31 a 1,38) Calidad de vida: Un solo estudio con 54 pacientes en el grupo de intervenci贸n y 55 en el de tratamiento usual, incluy贸 la medici贸n la calidad de vida con la escala EQ-5D al final del tratamiento y a mediano plazo 19 .…”
Section: Terapia De Adherenciaunclassified